2 - La politique publique de la gestion des espaces verts par l’hôtel de ville de Kinshasa - Ngur-Ikone, Jules Kassay (Africa Development, 2021)
In terms of the urban planning of the city of Kinshasa (capital of the DRC), the colonial authorities had planned to have green spaces to provide the urban living space with a greenery that would promote relaxation and beautify the city. The same public urban development policy continued to be applied from 1960 to 1980; but nowadays, with the population explosion, the green spaces that used to be the pride of the Congolese capital either wiped off the map or spoilt by slum dwellings on the pretext of reducing insalubrity and insecurity. The presence of small trades and spontaneous markets also promotes insalubrity. And it is all taking place under the helpless eyes of the governor of the city. Our aim is to demonstrate the importance of green spaces in the city landscape, to review the management of these spaces by the beneficiary populatio and by the urban authorities, and finally to propose a way forward..